A customised finn dinghy rudder for optimal olympic performance - Stadler, M.; Blinzler, B.; Persson, A.; Finnsgård, C.; Salminen, M.; Fagerström, M. (Proceedings, 2020)
Because of the long history of the Finn Dinghy sailing class, the difference between a gold medal and a mediocre result often comes down to personal mistakes of the sailor, or to who has the most optimised equipment. Regarding the latter, the Finn class rules permit certain design variations of the hull, mast, sail and rudder. In the current contribution, we describe a method for developing a customised rudder system aimed at optimal performance during the Tokyo 2020 Olympics. Based on hydrodynamic analysis of existing rudder designs, an improved rudder geometry was developed. Based on the concept geometry, the rudder and tiller were structurally designed and manufactured to achieve high stiffness and sufficient strength, while respecting the minimum mass requirements as specified by the rules.